Comparison of 177Lu-octreotate and 177Lu-octreotide for treatment in human neuroblastoma-bearing mice - A. Romiani; K. Simonsson; D. Pettersson; A. Al-Awar; N. Rassol; H. Bakr; D.E. Lind; G. Umapathy; J. Spetz; R.H. Palmer; B. Hallberg; K. Helou; et al. (Heliyon, 2024)
Background: Patients with high-risk neuroblastoma (NB) have a 5-year event-free survival of less than 50 %, and novel and improved treatment options are needed. Radiolabeled somatostatin analogs (SSTAs) could be a treatment option. The aims of this work were to compare the biodistribution and the therapeutic effects of 177Lu-octreotate and 177Lu-octreotide in mice bearing the human CLB-BAR NB cell line, and to evaluate their regulatory effects on apoptosis-related genes. Methods: The biodistribution of 177Lu-octreotide in mice bearing CLB-BAR tumors was studied at 1, 24, and 168 h after administration, and the absorbed dose was estimated to tumor and normal tissues. Further, animals were administered different amounts of 177Lu-octreotate or 177Lu-octreotide. Tumor volume was measured over time and compared to a control group given saline. RNA was extracted from tumors, and the expression of 84 selected genes involved in apoptosis was quantified with qPCR. Results: The activity concentration was generally lower in most tissues for 177Lu-octreotide compared to 177Lu-octreotate. Mean absorbed dose per administered activity to tumor after injection of 1.5 MBq and 15 MBq was 0.74 and 0.03 Gy/MBq for 177Lu-octreotide and 2.9 and 0.45 Gy/MBq for 177Lu-octreotate, respectively. 177Lu-octreotide treatment resulted in statistically significant differences compared to controls. Fractionated administration led to a higher survival fraction than after a single administration. The pro-apoptotic genes TNSFS8, TNSFS10, and TRADD were regulated after administration with 177Lu-octreotate. Treatment with 177Lu-octreotide yielded regulation of the pro-apoptotic genes CASP5 and TRADD, and of the anti-apoptotic gene IL10 as well as the apoptosis-related gene TNF. Conclusion: 177Lu-octreotide gave somewhat better anti-tumor effects than 177Lu-octreotate. The similar effect observed in the treated groups with 177Lu-octreotate suggests saturation of the somatostatin receptors. Pronounced anti-tumor effects following fractionated administration merited receptor saturation as an explanation. The gene expression analyses suggest apoptosis activation through the extrinsic pathway for both radiopharmaceuticals.